The Disulfiram/Copper Complex Induces Autophagic Cell Death in Colorectal Cancer by Targeting ULK1 - Yeting Hu (Frontiers Media S.A., 2021)
Colorectal cancer (CRC) is highly prevalent worldwide, but there has been limited development of efficient and affordable treatment. Induced autophagy has recently been recognized as a novel therapeutic strategy in cancer treatment, and disulfiram (DSF), a well-known antialcohol drug, is also found to inhibit tumor growth in various malignancies. Recently, DSF has been reported to induce excessive autophagy in oral squamous cells; however, little is known about whether it can induce autophagy and suppress proliferation in CRC. In this study, we investigate the effect of DSF with copper (DSF/Cu) on CRC both in vitro and in vivo and find that the combination significantly inhibits CRC cell viability and mainly induces autophagy instead of apoptosis. Furthermore, we use whole genome CRISPR library screening and identify a new mechanism by which DSF triggers autophagy by ULK1. Overall, these findings provide a potential CRC treatment.